Pemanfaatan Citra Sentinel-2 untuk Analisis Perubahan Kerapatan Vegetasi di Kecamatan Palaran Tahun 2019-2021 - M. Kurniawan; Nia Kurniadin; Hasanudin Hasanudin; Shabri Indra Suryalfihra (Journal of Geomatics Engineering, Technology, and Science, 2024)
Palaran is a sub-district in Samarinda City, East Kalimantan Province, with an area of approximately 221.29 km2. Palaran Sub-District is a place for various activities of residents and other areas around Samarinda City. These activities caused Palaran Sub-District to develop rapidly. The increasing need for housing is the cause of the conversion of green land as a vegetation area to other functions. Land conversion will increase along with population growth. The existence of vegetation in urban areas as green open space has many benefits, one of which is producing clean air. Apart from being an important element, vegetation also ensures that the ecosystem is not disturbed. The aim of this research is to determine changes in Vegetation Density in Palaran Sub-District and to determine the extent of changes in Vegetation Density in Palaran Sub-District. The Normalized Difference Vegetation Index (NDVI) method is used to analyze changes in vegetation density by utilizing Sentinel-2 imagery data recorded in 2019, 2020 and 2021. The results of the research are maps of changes in vegetation density and the magnitude of changes that occurred in Palaran Sub-District in 2019, 2020, 2021. Changes in density of high, medium, low, very low and non-vegetated vegetation from 2019 to 2021 respectively covering an area of 925.76 Ha, -160.52 Ha, -270.24 Ha, -654. 20 Ha, and 159.20 Ha. There was an increase in the density of high and unvegetated vegetation, as well as a decrease in the density of medium, low and very low vegetation. It is hoped that this information can be used as supporting data in efforts to control land conversion to maintain spatial planning and carrying capacity that is beneficial to the community.